Systematic review of carotid artery procedures and the volume–outcome relationship in Europe. Issue 10 (20th June 2017) - Phillips, P; Poku, E; Essat, M; Woods, H B; Goka, E A; Kaltenthaler, E C; Shackley, P; Walters, S; Michaels, J A
Abstract: Background: Hospitals that conduct more procedures on the carotid arteries may achieve better outcomes. In the context of ongoing reconfiguration of UK vascular services, this systematic review was conducted to evaluate the relationship between the volume of carotid procedures and outcomes, including mortality and stroke. Methods: Searches of electronic databases identified studies that reported the effect of hospital or clinician volume on outcomes. Reference and citation searches were also performed. Inclusion was restricted to European populations on the basis that the model of healthcare delivery is similar across Europe, but differs from that in the USA and elsewhere. Analyses of hospital and clinician volume, and carotid endarterectomy (CEA) and carotid artery stenting (CAS) were conducted separately. Results: Eleven eligible studies were identified (233 411 participants), five from the UK, two from Sweden, one each from Germany, Finland and Italy, and a combined German, Austrian and Swiss population. All studies were observational. Two large studies (179 736 patients) suggested an inverse relationship between hospital volume and mortality (number needed to treat (NNT) as low as 165), and combined mortality and stroke (NNT as low as 93), following CEA. The evidence was less clear for CAS; multiple analyses in three studies did not identify convincing evidence of an association. Limited data are available on the relationship between clinician volume and outcome in CAS; in CEA, an inverse relationship was identified by two of three small studies. Conclusion: The evidence from the largest and highest-quality studies included in this review support the centralization of CEA. Abstract : More justification for higher-volume centres